Du local à l’impérial : extorsion, insurrection et réforme dans le Haut-Pérou de Charles III (1759-1788) - Philippe Castejón (Caravelle)
During the decade of 1780, the increasing corruption among the judges of Charcas’ Audiencia caused a series of disturbances, including opposition among various representatives of royal authority, permanent conflict among oidores and Tomás Katari’s Indian revolt. As a consequence, half of the judges of Charcas’ Audiencia were dismissed and exiled. These events reveal a social history of politics with its multiple implications. They allow us to understand the interactions and the power game between royal representatives and local societies and show the hiatus between the “Bourbon Reforms” and their implementation.